Republika sociologů mezi analýzou a angažovaností: Ferdinand Peroutka jako veřejný sociolog? - Gramskopf, Rostislav (Lidé města, 2025)
This article examines how Ferdinand Peroutka’s texts reflect the tension between analytical detachment and engagement and to what extent his reflection on post-war changes can be interpreted as public sociology (Burawoy 2005). Within the framework of the Republic of Sociologists (Nešpor 2011), the study analyzes Peroutka’s journalistic work from 1945–1947 and his distinctive approach to democratic values and societal transformations. Through a qualitative content analysis of selected texts from Tak nebo tak (Peroutka 1947), the article illustrates how Peroutka oscillated between the factual analysis of structural changes and active participation in public debate. The study also reflects on the limitations of this interpretation – notably the omission of the institutional and cultural context (Kosatík 2011) – and opens perspectives for further research, particularly an exploration of the spiritual aspects of Peroutka’s reflexivity and a comparison of his approach with that of other public intellectuals of the time. This article thus contributes to the broader discussion on the role of intellectuals in the public sphere and the boundaries of (public) sociology.